Prevalence and risk factors of self-medication in pregnancy: A cross-sectional study from a tertiary care hospital in Eastern India - Mayank Gupta (Manipal College of Medical Sciences, Pokhara, 2021)
Background: Self-medication in pregnancy is a common but unsafe practice. There is a possibility of surreptitious exposure of the developing fetus to the teratogenic and abortifacient effects of the drugs.